Money management for college students by BudgetBuddy / Muhammad Nasrullah Abdul Aziz ... [et al.] - Abdul Aziz, Muhammad Nasrullah; Khairuddin, Sharul Adni; Daud, Mohammad Farez; Borhan, Halimahton (Universiti Teknologi MARA, Kedah, 2023)
College is often the first time that young people have to manage their own finances. Many students, however, lack the necessary skills for managing their own money. Financial difficulties, frequently the result of bad budgeting habits, are a major contributor to the high dropout rate among college students. Parents know that their kids need to know the basics about money, but many of them don't know how to teach their kids good money management skills. Parents should know that teaching their kids about money doesn't have to be hard or confusing. BudgetBuddy a website that offers student on how to manage their money and divide their money carefully to avoid overspending. The objectives to make sure student can be financially independent and know where to put their money. For example, BudgetBuddy provides a calculation that can calculate their money and automatically divided them into several places such as saving, wants and needs, foods, and bills and commitment. This helps student to manage their expenses and money effectively. This promotes financial independent among student and it corresponds to SULAM's objective of improving community well-being.